Injuries and complaints in the Brazilian national volleyball male team: a case study - Haupenthal, A.; Bufon, T.; dos Santos, M. C.; Matte, L. M.; Dell`Antonio, E.; Franco, F. M.; do Amaral, N. C. P.; dos Santos Costa, L.; Nunes, G. S. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The literature reports a vast amount of epidemiological information on injuries in volleyball athletes. However, little is known about the incidence of injuries in elite athletes of international level participating in major competitions, such as world championships and Olympic games. The objective of the study was to analyse the incidence of injuries in elite professional volleyball athletes, and the prevalence of complaints reported by athletes.